2015
DOI: 10.1587/transinf.2014icp0001
|View full text |Cite
|
Sign up to set email alerts
|

ROI-Based Reversible Data Hiding Scheme for Medical Images with Tamper Detection

Abstract: SUMMARYA novel ROI-based reversible data hiding scheme is proposed for medical images, which is able to hide electronic patient record (EPR) and protect the region of interest (ROI) with tamper localization and recovery. The proposed scheme combines prediction error expansion with the sorting technique for embedding EPR into ROI, and the recovery information is embedded into the region of non-interest (RONI) using histogram shifting (HS) method which hardly leads to the overflow and underflow problems. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Finally, research results showed that this design had a high reception capacity and high signal quality. 10 Liu et al 11 studied an ROI-based reversible data encryption design for maliciously manipulated medical images. The design presented in this article was suggested for medical images which can hide the patients' electronic files and protect the patients' information from manipulation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, research results showed that this design had a high reception capacity and high signal quality. 10 Liu et al 11 studied an ROI-based reversible data encryption design for maliciously manipulated medical images. The design presented in this article was suggested for medical images which can hide the patients' electronic files and protect the patients' information from manipulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The histogram shifting method was used in this article. 11 Xia et al 12 proposed an algorithm based on a novel quaternion polar complex exponential transform (NoQPCET) that was first constructed with effectively improved performance; then the NoQPCET and chaotic system-based robust color image zero-watermarking algorithm was suggested for lossless copyright protection of color images. In their study, the robustness against geometric attacks was enhanced due to the excellent geometric invariance of NoQPCET, and the security was also improved because of the initial value sensitivity of the chaotic system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Los archivos contienen datos clínicos de los pacientes que son la principal fuente de información para el diagnóstico y tratamiento de una gran cantidad de enfermedades y anomalías. Al mismo tiempo que existen estos beneficios también existen riesgos para los datos o registros electrónicos paciente o EPR (Electronic Patient Record, por sus siglas en inglés), por lo tanto, es una necesidad constante el mantener la seguridad de la información en imágenes médicas [3,4].…”
Section: Introductionunclassified